Categorial features : a generative theory of word class categories - Panagiotidis, Phoevos (Cambridge : Cambridge University Press, 2015)
'Proposing a novel theory of parts of speech, this book discusses categorization from a methodological and theoretical point a view. It draws on discoveries and insights from a number of approaches - typology, cognitive grammar, notional approaches, and generative grammar - and presents a generative, feature-based theory. Building on up-to-date research and the latest findings and ideas in categorization and word-building, Panagiotidis combines the primacy of categorical features with a syntactic categorization approach, addressing the fundamental, but often overlooked, questions in grammatical theory. Designed for graduate students and researchers studying grammar and syntax, this book is richly illustrated with examples from a variety of languages and explains elements and phenomena central to the nature of human language'--
Includes bibliographical references (p. 189-203) and index.
Keywords: Grammar, Comparative and general -- Grammaticalization; Categorial grammar; Language, Universal